2002
DOI: 10.1038/sj.bjc.6600121
|View full text |Cite
|
Sign up to set email alerts
|

Phase II multicentre study of docetaxel plus cisplatin in patients with advanced urothelial cancer

Abstract: A multicentre phase II trial was undertaken to evaluate the activity and toxicity of docetaxel plus cisplatin as first-line chemotherapy in patients with urothelial cancer. Thirty-eight patients with locally advanced or metastatic transitional-cell carcinoma of the bladder, renal pelvis or ureter received the combination of docetaxel 75 mg m 72 and cisplatin 75 mg m 72 on day 1 and repeated every 21 days, to a maximum of six cycles. The median delivered dose-intensity was 98% (range 79 -102%) of the planned do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Phase II trials of patients with advanced bladder cancer treated with the combination of a taxane and cisplatin have reported response rates (RRs) of 52-70%, times to progression of 5-7 months, and OS of 8-14 months, with a safety profile consistent with that reported in patients with other solid tumors [10,11,12,13,14]. However, a phase III trial conducted by the Hellenic Cooperative Oncology Group found that docetaxel in combination with cisplatin was less effective than M-VAC (both regimens given with prophylactic granulocyte colony-stimulating factor) in terms of RR, progression-free survival (PFS), and OS [15].…”
Section: Introductionmentioning
confidence: 72%
“…Phase II trials of patients with advanced bladder cancer treated with the combination of a taxane and cisplatin have reported response rates (RRs) of 52-70%, times to progression of 5-7 months, and OS of 8-14 months, with a safety profile consistent with that reported in patients with other solid tumors [10,11,12,13,14]. However, a phase III trial conducted by the Hellenic Cooperative Oncology Group found that docetaxel in combination with cisplatin was less effective than M-VAC (both regimens given with prophylactic granulocyte colony-stimulating factor) in terms of RR, progression-free survival (PFS), and OS [15].…”
Section: Introductionmentioning
confidence: 72%
“…Several phase II trials have shown that newer drugs, such as paclitaxel and docetaxel, have potential as single agents or in combination in the treatment of metastatic urethelial cancer [30][31][32][33]. Carboplatin has also been tested in patients with renal dysfunction [31,32].…”
Section: New Chemotherapeutic Agentsmentioning
confidence: 98%
“…In a multicenter phase II trial, 38 previously untreated patients with advanced/metastatic TCC received docetaxel 75 mg/m 2 and cisplatin 75 mg/m 2 every 21 days [10]. There were seven (19%) complete responses and 15 (39%) partial responses for an overall response rate of 58% (95% CI, 41%-74%).…”
Section: Docetaxel Plus Cisplatinmentioning
confidence: 99%